Health Communication Strategies in Dengue Fever Prevention at Wonokusumo Health Center Surabaya - Satrio Bagas Prakoso; Moh Agung Kurniawan (Literasi Nusantara, 2026)
This study aims to analyze the implementation of health communication strategies as well as the supporting and inhibiting factors affecting communication effectiveness in the Dengue Hemorrhagic Fever (DHF) prevention program at the Wonokusumo Community Health Center (Puskesmas) in Surabaya. This study employs a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, interviews, and documentation involving healthcare workers, health volunteers (kader), and community members participating in the DHF prevention program. The results indicate that the health communication strategy is executed through health counseling, "3M Plus" socialization, fogging, mosquito larva inspection, environmental cleanup, and the empowerment of larva monitoring volunteers (jumantik) and the Kampung Surabaya Hebat (KSH) volunteers. This communication strategy is implemented participatively and collaboratively by involving schools, local neighborhood heads (RT/RW), health volunteers, and the surrounding community. Supporting factors for the strategy's effectiveness include cross-sector cooperation, the active involvement of health volunteers, and interpersonal communication that is easily understood by the public. Meanwhile, inhibiting factors include low participation from some community members, a lack of consistency in maintaining environmental cleanliness, and limitations in health promotion media. This study concludes that a health communication strategy based on community participation and health volunteer empowerment can successfully increase public knowledge, awareness, and participation in DHF prevention within densely populated urban areas. Therefore, it is necessary to strengthen health communication media and provide continuous education so that the DHF prevention program can run more effectively and sustainably.